Database of identified disruptive seeds in Guatemala - Marieke Veeger; Lucas Rutting (2023)
Using a snowball technique, 75 Seed Initiatives were identified in Guatemala during 2022. 23 of these seeds were prioritized by considering if they; are situated in the most climate vulnerable regions; challenge current power structures; offer more just or sustainable alternatives to current systems or practices (i.e. if they provide ideas for transformation); (in) explicitly aim for new forms of governance or institutional change; are they related to food systems or nutrition; and if they are focused on or led by women, youth, and/or indigenous people or campesinos. This resulted in a database of the the most disruptive and promising seeds from Guatemala´s most climate vulnerable regions. These prioritised disruptive seeds were invited to participate in developing transformation pathways for Guatemala´s food system.